Variants of Proper Names in Epistolary Heritage of Lesia Ukrainka (Linguostylistic Studies, 2016)
This article analyzes the variants of proper names revealed in Lesia Ukrainka’s letters to her family and friends. The emphasis is laid on word-building peculiarities of the names’ variants that have emerged as a result of either suffixation of full and reduced stems of the official names or by reducing and reducing-suffixal way including their diverse combinations. The author also points to the cases of russificated names variants like Grysha, Sasha, Shura occurring in the letters of Lesia Ukrainka.According to the findings of this study, female proper names versions quantitatively dominate over the male names, since Lesia Ukrainka corresponded mostly with women. The study revealed 18 affixes (-атк-о, -ик, -к-о, -унь-о, -унк-у, -утк-о, -о and others), by which the male names are formed and 26 variants of female names (-кa, -кo, -очка, -очко,  -унька, -ися,  -ня,  -уся and others). Some of the suffixes are involved in various types of word formation, others – just only in one. Although these proper names for the most part are of the same derivation as the Volyn-Polissian, they still manifest their specificity. The colloquial version Mika of the name Dmytro or Ima from Eugeniia, used only in the family circle of the Kosachys, are classified as identifying suffixes. Both male and reduced female variants of names are formed by adding affixes -ка, -ся, -чик. Key words: proper names, variants, epistolary heritage, derivational suffixes, word building analysis. References